2001
DOI: 10.1007/s003300000616
|View full text |Cite
|
Sign up to set email alerts
|

The value of endorectal MR imaging to predict positive biopsies in clinically intermediate-risk prostate cancer patients

Abstract: The aim of this study was to assess the effectiveness of endorectal MR imaging in predicting the positive biopsy results in patients with clinically intermediate risk for prostate cancer. We performed a prospective endorectal MR imaging study with 81 patients at intermediate risk to detect prostate cancer between January 1997 and December 1998. Intermediate risk was defined as: prostatic specific antigen (PSA) levels between 4 and 10 ng/ml or PSA levels in the range of 10-20 ng/ml but negative digital rectal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…The sensitivity for the detection of a PCa by e-MRT varies between 50 and 93%, depending on the study, and compared with TRUS, e-MRI offers a clearly higher sensitivity for the detection of a prostate tumor. 23 Vilanova et al 24 showed a specificity of 76% and a sensitivity of 70% for prediction of positive PB using unenhanced MRI in a group of 81 patients. He performed a 6-core PB based on the findings and reported a 28% of PCa.…”
Section: Discussionmentioning
confidence: 98%
“…The sensitivity for the detection of a PCa by e-MRT varies between 50 and 93%, depending on the study, and compared with TRUS, e-MRI offers a clearly higher sensitivity for the detection of a prostate tumor. 23 Vilanova et al 24 showed a specificity of 76% and a sensitivity of 70% for prediction of positive PB using unenhanced MRI in a group of 81 patients. He performed a 6-core PB based on the findings and reported a 28% of PCa.…”
Section: Discussionmentioning
confidence: 98%
“…Perrotti et al (25) and Vilanova et al (26) proposed the idea that prostate adenocarcinoma can be imaged by MRI and, studying the prospective use of MRI to guide biopsy, they showed a slight benefit with a sensitivity of 70% to 83% and a PPV of 12% to 53%. Yuen et al…”
Section: Discussionmentioning
confidence: 99%
“…High resolution T2-weighted TSE (TR/TE=4400/109 ms; 3-mm section thickness) sequences using the combination of spine coil and small surface coil showed a higher anatomic resolution of the prostate gland (d) For these reasons some authors used MRI findings for the guidance of biopsies of the prostate gland. Some authors used the results of endorectal MR imaging to guide the placement of needles during TRUS guided biopsies of the areas of suspicion detected by MR imaging [32,33]. Kaplan et al performed ultrasound-MR image fusion for better results in directing biopsies of abnormal areas determined in high-field-MR images [7].…”
Section: Discussionmentioning
confidence: 99%